Soil Excavation by Desert Gerbil Meriones Hurrianae (Jerdon) in the Shekhawati Region of Rajasthan Desert - Sharma, V N; Joshi, M C (Annals of Arid Zone, 2016)
Investigations on soil excavation and burrows in cultivated and uncultivated condition by Desert Gerbil. Meriones hurrianas(Jerdon) around Pilani in May-June, 1972 reveal that the total number of openings of gerbil burrows are about 2,0O,OOO/sq km and 4,40,000/sq, km. in cultivated and uncultivated areas respectively. Total number of burrow openings for active soil excavation was about 80.000/sq km/day and 6O,000/sq. km,/day in cultivated and uncultivated areas respectively. Soil excavated was about 61,500 kg per day and 41,60,000 cc/day by volume per sq, km on cultivated area as ai4lst 10,43,800 kg./day and 7,06,80,000 cclday in the un-cultivated area. The record for temperature at 45 em inside the burrow and soil moisture reveals that the soil excavation is directly related to these factors.